ДО ПИТАННЯ ПРО МЕТОДОЛОГІЧНІ ПІДХОДИ ЩОДО ОРГАНІЗАЦІЇ ВІДТВОРЕННЯ ПРОДУКТИВНИХ СИЛ - Vasylenko, V.M.; Budyakov, V.E. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2008)
Through the prism of modern paradigm "region-system" the methodological premises for organization of reproduction of productive forces are considered on a scale of a separate region. The process of organization of reproduction of elements of productive forces is offered to be provided taking into account requirements of either conceptions of reproduction approach (taking into account the regional features of cycle of reproduction), or conceptions of investment climate (taking into account the investment attractiveness of region) or their combinations.